Microscopical diagnostic elements of leaves of Ginkgo biloba L. and herbs of a Filipendula ulmaria (L.) Maxim . in the tablets «GINKGOTROPIL» - J. V. Daironas; A. V. Korochinsky; I. N. Zilfikarov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
The microscopical diagnostic elements of powdered raw materials in the tablets «GINKGOTROPIL » were studied. It was concluded that the tablets «GINKGOTROPIL» contain the leaves of Ginkgo biloba L. and the herbs of a Filipendula ulmaria (L.) Maxim. Diagnosis of anatomic signs of plant components allows for the standardization of the drug in terms of «Microscopy».